Factors a ecting church members retention in the Texas Conference of Seventh-Day Adventists - Miranda, Juan Carlos Niño de; Jean-Charles, William Joseph (Anuario de Investigación UM, 2020)
The ability to retain its membership post baptism appears to be a great challenge for the Seventh-day Adventist church. Several studies have revealed that one out of every three neophytes leave the church post baptism. This empirical model hypothesizes that transformational leadership, culture, church programs and evangelism are factors that can predict members’ retention post baptism at the Texas Conference of Seventh-day Adventist Church in Alvarado, Texas, USA.